Highly reproducible, simple and selective analytical method for extractive UV-visible spectrophotometric determination of ruthenium (III): analysis of catalyst, fissium alloy and sequential separation - Shaikh, Abdul B.; Barache, Umesh B.; Khogare, Balaji T.; Goswami, Ritusmita; Kokare, Balasaheb N.; Wadgaonkar, Prakash P.; Gaikwad, Shashikant H. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2020)
An easy and selective method has been developed for the extractive spectrophotometric determination of ruthenium(III) with 4-(4'-flurobenzylideneimino)-3-methyl-5-mercapto-1,2,4-triazole (FBIMMT) as a chelating reagent. The basis of the method is the formation of stable complex of `soft base' FBIMMT with `soft acid' ruthenium(M). The reagent FBIMMT in n-butanol easily forms extractable yellow coloured complex with ruthenium(III) in acetate buffer of pH 4.8. The absorbance of [Ru(III)-FBIMMT] complex is measured at 394 nm against the reagent blank. Good linearity range of concentration up to 27.0 mu g mL(-1) of ruthenium(III) is attained with correlation coefficient R-2 = 0.998. The optimum concentration range is 6 to 27.0 mu g mL(-1) which is deduced by Ringbom's plot. The apparent molar absorptivity found to be 2.75 x 10(3) L mol(-1) cm(-1). Some additional characteristics such as limit of detection (LOD = 0.48 mu g mL(-1)), limit of quantification (LOQ = 1.19 mu g mL(-1)), and Sandell's sensitivity (SS = of 0.0367 mu g cm(-2)) arc also estimated. The composition of [Ru (III)-FBIMMT1 complex has been established from Job's continuous variation method, mole ratio method, and log-log plot method. The specificity towards ruthenium(III) is well studied and appropriate masking agents are applied wherever required to boost it. The intra-day and inter-day precision values are found to be brilliant with % relative standard deviation of 0.52 and 0.68 respectively with % accuracy within the range of 99.00-100. The method is effectively used for determination of ruthenium(III) from water samples, binary and ternary synthetic mixtures, fissium alloy samples and catalyst materials. A scheme for sequential group separation of ruthenium(III), palladium(II) and osmium (VIII) has also been developed. The reproducible results of the present method confirm that the method has a good potential for quantitative determination of ruthenium(III) from various matrices. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alloy samples; FBIMMT; Ruthenium(III); Spectrophotometric determination; Synthetic mixtures